Optimalisasi Peran Dosen Pendamping Program dalam Mendampingi Mahasiswa Studi Independen Perkumpulan Sosial Ekonomi Akselerator Lab (SEAL) Malang pada Program Magang dan Studi Independen Bersertifikat (MSIB) Angkatan 7 - Nurjayanti, Nurjayanti; Fadhillah. S, Nurul; Bt Samsuddin, Yati; Sanmas, Masni (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
The gap between students’ theoretical competencies in higher education and the practical skills required in the professional and industrial world has driven the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) during the Kabinet Indonesia Maju 2019–2024 period to initiate the Certified Internship and Independent Study Program (MSIB). This program is part of the Merdeka Belajar–Kampus Merdeka (MBKM) curriculum and involves students, industry partners, supervising lecturers, and university coordinators. This community service activity focuses on optimizing the role of the Program Supervising Lecturer (Dosen Pendamping Program/DPP) in ensuring that all learning experiences gained by students during internships align with each study program’s learning outcomes (CPL). The activity was conducted at Perkumpulan Sosial Ekonomi Akselerator Lab (SEAL) Malang using an active mentoring strategy consisting of three stages: preparation, implementation, and evaluation. A total of 46 students participated in two roles—Content Creator & Communication Strategic and AWS Certification (Full Stack Cloud Engineering)—for one semester. The results indicate that structured and intensive mentoring significantly enhanced learning effectiveness, strengthened students’ competencies, and bridged the gap between academic curricula and industry needs. Thus, the role of the Supervising Lecturer is proven to be essential in supporting the successful implementation of the MSIB program.